Natural Killer Cells Contribute to Pathogenesis of Severe Alcoholic Hepatitis by Inducing Lysis of Endothelial Progenitor Cells. (5th December 2019) - Sehgal, Rashi; Kaur, Savneet; Shasthry, Saggere Murli; Agrawal, Tanvi; Dwivedi, Varsha; Seth, Devanshi; Ramakrishna, Gayatri; Sarin, Shiv Kumar; Trehanpati, Nirupma
Abstract : Background: Endothelial progenitor cells (EPCs) help in neovascularization and endothelial repair during injury. Patients with cirrhosis show increased number and function of EPCs in circulation. Methods: Since natural killer (NK) cells regulate EPCs, we investigated the relationship between the 2 in alcoholic cirrhosis (AC, n  = 50) and severe alcoholic hepatitis (SAH, n  = 18) patients and compared with nonalcoholic cirrhosis ( n  = 15) and healthy controls (HC, n  = 30). Levels of systemic inflammatory cytokines were measured, and coculture assays were performed between EPCs and NK cells in contact‐dependent and contact‐independent manner. NK cell–mediated killing of EPCs was evaluated, and expression of receptors including fractalkine (FKN) on EPCs and its cognate receptor CX3CR1 on NK cells was studied by RT‐PCR assays. Results: Patients with SAH had higher regulated on activation, normal T cell expressed and secreted (RANTES) ( p  = 0.01), vascular endothelial growth factor (VEGF) ( p  = 0.04), IL‐1β ( p  = 0.04), and IL‐6 ( p  = 0.00) growth factors and proinflammatory cytokines as compared to AC and HC. Distinct populations of CD31+ CD34+ EPCs with low and high expression of CD45 were significantly lower in SAH than HC (CD45 low, p  = 0.03; CD45 hi, p  = 0.04) and AC (CD45 low, p  = 0.05; CD45 hi, p  = 0.02). SAH patients, however, showed increased functional capacity of EPCs including colony formation and LDL uptake. NK cells were reduced in SAH compared with AC ( p  = 0.002), however with higher granzyme ability ( p  < 0.001 and p  = 0.04, respectively). In SAH, EPC‐NK cell interaction assays showed that NK cells lysed the EPCs in both contact‐dependent and contact‐independent assays. Expression of interaction receptor CX3CR1 was significantly higher on NK cells ( p  = 0.0005), while its cognate receptor, FKN, was increased on EPCs in SAH patients as compared to HC ( p  = 0.0055). Conclusion: We conclude that in SAH, NK cells induce killing of EPCs via CX3CR1/FKN axis that may be one of the key events contributing to disease severity and proinflammatory responses in SAH. Abstract : Alcohol results in profound damage to the vascular structure, however the mechanisms are unclear. The present work on Severe Alcoholic hepatitis (SAH) highlights the role of CX3CR1/Fractalkine axis in endothelial progenitor cell (EPCs) damage [i.e CD31+CD34+ on CD45low and CD45high] via the Natural Killer (NK) cells, thereby leading to strong inflammatory response.